Evaluation of the Lajnah Bahtsul Masail Program Using the CIPP Model at Al-Luqmaniyyah Islamic Boarding School Yogyakarta - Rangga Pratama Saputra; Suwadi Suwadi; Muh Nur Fuadi; Ahmad Mustofa (Journal Educational Research and Development | E-ISSN : 3063-9158, 2026)
This study aims to evaluate the Lajnah Bahtsul Masail (LBM) Program at Pondok Al- Luqmaniyyah Islamic Boarding School Yogyakarta (PPLQ) uses Stufflebeam's CIPP evaluation model (Context, Input, Process, Product). Although PPLQ already possesses the 2026 LBM Technical Guidelines as a written SOP, a comprehensive evaluation of input readiness and procedural implementation consistency in practice has never been conducted. The study employs a qualitative-evaluative approach, with data collected through document analysis, in-depth interviews, and participatory observation. Data validity was verified through source triangulation. Findings indicate: (1) contextually, LBM represents a strategic transformation from informal study into a structured intellectual forum; (2) in terms of input, human resources and facilities are available, yet the capacity of formulators requires strengthening; (3) procedurally, of five evaluated SOP aspects, one was found compliant, three partially compliant, and one non-compliant particularly regarding digital form submission via Google Form; (4) in terms of product, LBM produces documented fiqh decisions and improved student literacy competence in classical texts. These findings imply the urgency of strengthening digital infrastructure and human resource development as prerequisites for modernizing Islamic studies governance in Islamic boarding schools